Acoustic impedance inversion for geotechnical evaluation in underground coal mining - Hatherly, P.; Zhou, B.; Peters, T.; Urosevic, Milovan (2018)
Copyright © (2008) by the Society of Exploration Geophysicists All rights reserved. In underground coal mining, knowledge of the geomechanical properties of the strata surrounding the mining horizons is essential for the prevention of unexpected rock failures that can disrupt production and jeopardize mine safety. Model based acoustic impedance inversion integrates drill hole and seismic information to allow assessment of the geomechanical environment. We demonstrate our approach using results from a 3D and a 2D seismic survey. We introduce a means of converting acoustic impedance to the Geophysical Strata Rating (GSR). The GSR is a rock mass rating scheme that is normally derived from geophysical logging data. When expressed in terms of GSR, acoustic impedances have values that are meaningful to coal mine engineers.